Design of a randomised controlled trial of the effects of empagliflozin on myocardial perfusion, function and metabolism in type 2 diabetes patients at high cardiovascular risk (the SIMPLE trial). Issue 11 (27th November 2019) - Jürgens, Mikkel; Schou, Morten; Hasbak, Philip; Kjær, Andreas; Wolsk, Emil; Zerahn, Bo; Wiberg, Mikkel; Brandt, Niels Høgh; Gæde, Peter Haulund; Rossing, Peter; Faber, Jens; Inzucchi, Silvio; et al.
Abstract : Introduction: A diagnosis of type 2 diabetes (T2D) more than doubles the risk of cardiovascular disease (CVD), with heart failure (HF) being one of the most common complications with a severe prognosis. The landmark Empagliflozin Cardiovascular Outcome Event Trial in Type 2 Diabetes Mellitus Paitients (EMPA-REG OUTCOME) study demonstrated that treatment with the sodium glucose cotransporter-2 (SGLT-2) inhibitor empagliflozin rapidly and significantly reduces CVD mortality and admission rates for HF. However, the mechanisms behind this reduction in clinical events are unknown. This study was designed to investigate the effects of the SGLT-2 inhibitor empagliflozin on myocardial perfusion and function in patients with T2D and high CVD risk. Methods and analysis: In this investigator-initiated, randomised, double-blind controlled clinical trial, 92 patients with T2D and established CVD or high CVD risk will be randomised to treatment with empagliflozin 25 mg or a matching placebo for 13 weeks. The primary outcome measure is change in myocardial flow reserve measured quantitatively by Rubidium-82 position emission tomography. In a substudy, invasive haemodynamics at rest and during exercise will be measured at baseline and following the intervention, using right heart catheterisation. Ethics and dissemination: The study protocol (v7, 02/08/2018) has been approved by the Ethics Committee of the Capital Region, Danish Data Protection Board and the Danish Medicines Agency, and it will be monitored according to the Good Clinical Practice regulations from the International Conference on Harmonization. The results be submitted to international peer-reviewed journals and be presented at conferences. The data will be made available to the public via EudraCT and www.clinicaltrials.gov . Trial registration number: NCT03151343 .